Evaluating IT Delivery Value in the Faculty of Industrial Engineering at Telkom University Using the COBIT 2019 Framework, Domain APO04, for Mapping LAM INFOKOM Standards - Fasya, Muhammad Haikal; Lubis, Muharman; Abdurrahman, Lukman; Garcia-Constantino, Matias; Abdulmana, Sahidan; Ramadhani, Rafian (Yayasan Asmin Intelektual Berkah, 2024)
In the contemporary landscape, technology holds pivotal significance across diverse domains, including academia and industry. The Faculty of Industrial Engineering at Telkom University faces challenges in optimizing the value derived from its IT investments to meet evolving market demands. To address this, IT governance methodologies are essential, ensuring effective and secure IT utilization aligned with strategic objectives. This study investigates and evaluates the IT delivery value process at the Faculty of Industrial Engineering, Telkom University, using the COBIT 2019 Domain APO04 framework and LAM INFOKOM standards. Data collection involved primary interviews and secondary document analysis. The analysis revealed gaps in assessing emerging technologies and recommending further initiatives. Recommendations span people, process, and technology aspects, aiming to enhance technology evaluation procedures and documentation. This study provides insights into effectively leveraging IT to achieve the Faculty's objectives and enhance decision-making quality.